AICCRA Communications Strategy 2024-2026 - Bucknall-Williams, Rhys; Harrys, Amy (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
This AICCRA Communications Strategy (2024 – 2026) presents a detailed strategy and workplan to guide the work of its global communications team, as they build on the legacy of AICCRA’s inaugural phase (2021 – 2023) to deepen and broaden their partnerships across Africa in scaling CIS and CSA through the project’s additional finance phase (2024-2026). The strategy itself is informed by the experience and lessons learned from that first phase, as AICCRA initially took a flexible, iterative, and experiential approach to communications – testing what worked and what didn’t. As partnerships were forged and implementation gathered pace, so we enhanced the communications team, defined (and refined) our strategic and operational approach, and found our voice. This strategy supports the team in raising our ambition in additional finance to produce targeted, informative, and ultimately persuasive stories which catalyze the uptake and use of CGIAR innovations on a massive scale to address the climate crisis in Africa.